Physicochemical properties of pectin extracted from jackfruit and chempedak fruit rinds using various acids - Leong, C. M.; Mohd Adzahan, Noranizan; Syed Muhammad, Sharifah Kharidah; Choo, Wee Sim (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
This study investigated the effect of citric, nitric and sulfuric acid on the yield and physicochemical properties of pectin extracted from jackfruit and chempedak fruit rinds. Yield and physicochemical properties such as uronic acid content, degree of esterification, degree of acetylation and colour of pectin solution were determined and compared. Yield of pectin from jackfruit and chempedak fruit rinds with nitric acid as extractant were 14.81 ± 1.02% and 17.62 ± 0.69%, respectively, which were the lowest. The uronic acid content of all extracted pectin was more than 65%. All jackfruit and chempedak fruit rind pectins in this study were high methoxyl pectin with degree of esterification ranging from 72-75% for jackfruit rind pectin and 66-69% for chempedak rind pectin. The degree of acetylation of all extracted pectin was lower than 1%. For both jackfruit and chempedak fruit rind pectins, the citric acid-extracted pectin produced darker, more reddish and yellowish solution and thus is least preferable. Among the acids studied, sulfuric acid was the best extractant due to the high yield of pectin and the solution of this pectin was brighter, less reddish and yellowish.